THE CONSISTENCY OF IMAM SYAFI'I'S QIRAAT AND ITS INFLUENCE ON LEGAL ISTINBAT - ALIM, KHOZINUL (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2025)
The Qur'an was revealed to Prophet Muhammad with various readings. Although, on the one hand, this difference makes it easier for Muslims to recite the Qur'an, on the other hand, in some cases, the difference in reading influences the difference in meaning. One of the differences lies in the verses about jurisprudence issues, where the differences in the readings influence the legal interpretation. This article will discuss the problem of the consistency of Imam asy-Syāfi'ī's recitations in legal istinbat. By using a content analysis knife accompanied by the science of qiraat approach, the results of this research explain that in the problem of qiraat or recitation of the Qur'an, Imam asy-Syāfi'ī used the qiraat of Imam Ibn Kaṡīr with a history of erroneous readings from al-Qasṭanṭin. However, Imam asy-Syāfi'ī's choice of qiraat does not make him consistent with the qiraat in the legal sense. He sometimes uses other recitations in legal interpretation where the choice of Imam asy-Syāfi'ī is only in the optional realm and not in the realm of preference because all recitations are considered correct as long as they are connected to the Prophet Muhammad ﷺ Differences in recitations that bring influence to differences in meaning such as pronunciation.